The Relation Ship Between Management Process and Performace of RTA in UAE Technological Orientation as Moderator - Al Ali, Abdalla Ahmed Hassan; Nek kamal bin Yeop Yunus, (European Journal of Multidisciplinary Studies, 2020)
Transportation in United Arab Emirates (UAE) have contributed largely to economic output, import, and export in the manufacturing sector, creating employment opportunities in service sectors and expanding the export base. They are playing a role of key service providers and vendors to many big corporations. The significance of the contributions of project management process in Road and Transportation internationally and encourages more development initiative to support road and transportation from Middle Eastern region and United Arab Emirates (UAE). This study investigates the project management process, technological orientation and organizational performance of Infrastructure in United Arab Emirates (UAE). The size of the sample is designed with a view to establish the internal and external validity in order to generalize the findings to the population. As the study used Structural Equation Modelling, a higher sample above 400 was considered. A total of 436 responses were considered for the final analysis of the study.
Keywords: Technological orientation, Management process, performance.